The Effect of Innovation Practices on Business Resilience with External Support as a Moderating Variable in MSMEs at the Kasongan Pottery Industry Center - Dwisty Betary Refistia Lubis; Sabihaini Sabihaini; Irhas Effendi (PT. Publikasiku Academic Solution, 2025)
This study aims to determine the influence of innovation practices on business resilience with external support as a moderation variable in SMEs in the Kasongan Pottery Industry Center, Bantul Regency. The population in this study is all SMEs in the Kasongan Pottery Industry Center, Bangunjiwo Village, Bantul Regency. The sampling technique uses a census technique where the entire population is used as a research sample with a total of 80 SMEs. The analysis methods used in this study are descriptive analysis and quantitative analysis. This research was conducted using the Moderating Regression Analysis method through the analysis tool used, namely SPSS (Statistical Product and Service Solution) 25. The results of this study are (1) Innovation practices have a significant and positive effect on business resilience; (2) External support does not moderate the influence of innovation practices on business resilience.